(untitled) (Torani Journal of Fisheries and Marine Science, 2016)
his research was conducted in November to December 2012 which aimed to estimate the population dynamic of mackerel fish through their age-group, growth, mortality, and yield per recruitment. Samples were taken from the waters of sub district of Panyula, in the district of East Tanete Riatang, in Bone Region. Age-group was measured using Bhattacharya method with the help of Fish Stock Assessment Tools II (FISAT II) software. Growth and natural mortality were measured by applying the equations of Von Bertalanffy and Empiris Pauly (respectively). Whereas total mortality as well as yield per recruitment were estimated by applying Beverton and Hold equation; and catch mortality was estimated by applying the equation of Z=F+M. Results showed the average total length of 849 mackarel fish that was 121-295 mm. They were divided into 4 groups with 306.35 mm asymptotic length, 0,33 growth rate coefficient and theoritical age of 0.0294 year. Natural mortality rate, total and catch mortality, and exploitation rate were 0.3672 per year; 2,4358 per year, 2,0687 per year and 0.8493 (respectively). This indicated that an over catch had occurred due to the higher catch mortality compared to the natural mortality as well as the yield per recruitment, i.e. 0.0865 gram/recruitment. Keywords : Population dynamic, mackerel fish, Bone Strait.